End‐of‐life care in an Australian acute hospital: a retrospective observational study. Issue 11 (11th November 2019) - Maubach, Ninya; Batten, Monique; Jones, Scott; Chen, Judy; Scholz, Brett; Davis, Alison; Bromley, Jonathan; Burke, Brandon; Tan, Ren; Hurwitz, Mark; Rodgers, Helen; Mitchell, Imogen
Abstract: Background: There is a gap in knowledge about the kind and quality of care experienced by hospital patients at the end of their lives. Aims: To document and compare the patterns in end‐of‐life care for patients dying across a range of different medical units in an acute care hospital. Methods: A retrospective observational study of consecutive adult inpatient deaths between 1 July 2010 and 30 June 2014 in four different medical units of an Australian tertiary referral hospital was performed. Units were selected on the basis of highest inpatient death rates and included medical oncology, respiratory medicine, cardiology and gastroenterology/hepatology. Results: Overall, 41% of patients died with active medical treatment plans, but significantly more respiratory and cardiology patients died with ongoing treatment (46 and 75% respectively) than medical oncology and gastroenterology patients (each 27%, P < 0.05). More medical oncology and gastroenterology patients were recognised as dying (92 and 88%) compared with 72% of respiratory and only 38% of cardiology patients ( P < 0.001). Significantly, more medical oncology patients were referred to palliative care and received comfort care plans than all other patient groups. However, the rate of non‐palliative interventions given in the final 48 h was not significantly different between all four groups. Conclusions: There were differences in managing the dying process between all disciplines. A possible solution to these discrepancies would be to create an integrated palliative care approach across the hospital. Improving and reducing interdisciplinary practice variations will allow more patients to have a high‐quality and safe death in acute hospitals.